Frontiers in Plant Breeding: Perspectives for the Selection of Vegetables Less Susceptible to Enteric Pathogens - Henriquez, Tania; Lenzi, Anna; Baldi, Ada; Marvasi, Massimiliano (Frontiers in Microbiology, 2020)
Fresh vegetables including baby greens, microgreens and sprouts can host human pathogens without exhibiting any visible signs of spoilage. It is clear that the vast majority of foodborne disease outbreaks associated with vegetable produce are not simply a result of an oversight by a producer, as it was shown that zoonotic pathogens from Enterobacteriaceae can contaminate produce through various routes throughout the entire production cycle. In this context, phenotypic and genotypic signatures have been used since early ages in agriculture to obtain better produce, and can be used today as a strategy to reduce the risk of outbreaks through plant breeding. In this mini-review, we provide an updated view and perspectives on to what extent the selection of biological markers can be used to select for safer cultivars of vegetable crop such as tomato (the more studied), leafy greens and cabbage. Once this knowledge will be better consolidated, these approaches should be integrated into the development of comprehensive farm-to-fork produce safety programs.